Letter (copy) : International Solidarity Fund: help for Spain - Tewson, Vincent
032-0086-001 Secretary's. HVT/FC/353. 6th March, 1939. Mr. Austen Albu, Hon. Treasurer, The Labour Spain Committee, 20, East Heath Road, N.W.3. Dear Mr. Albu, INTERNATIONAL SOLIDARITY FUND - HELP FOR SPAIN. With reference to my letter of the 3rd instant the Transfer Note for £150 has now been received from the Bank, and I have much pleasure, therefore, in enclosing our receipt for that amount. Will you please convey to your Committee our best thanks for their continued help which I can assure you is much appreciated. Yours sincerely, Assistant Secretary. Receipt. 292/946/32/86